Academic library repository access policy in Indonesia: recent policy updates - Araf Aliwijaya; Adzkiyah Mubarokah; Nicky Yasmidar; Ari Suryadi; Nurrahma Yanti; Anggi Saputra; Yoan Berliana Siregar (Priviet Social Sciences Journal, 2026)
This study aims to identify repository access policies in university libraries in the Special Region of Yogyakarta. A qualitative approach was used through in-depth interviews. Eight informants from four selected libraries, as well as observation and review of repository websites. The results show a wide variety of policies ranging from full open access, limited access per chapter, access only for institutional members through Single Sign-On, to access restrictions only through library computers, as well as take-down and embargo practices. The findings report a general chronological pattern, namely initialization with openness, then gradually restricted due to concerns about plagiarism, protection of sensitive data, administrative burdens, resource limitations, and encouragement from internal actors such as lecturers. The discussion emphasizes that the reality of policy in the field is more complex than the typology in the literature because it is simultaneously influenced by technical, normative, and administrative factors. This research is expected to serve as a guideline for contextual and consistent repository policies, strengthening technical and managerial capacity, copyright policies, and communication strategies to increase researcher participation. Recommendations include the development of integrated embargo and authentication mechanisms to balance open access and the protection of academic integrity.